High performance polypropylene nanocomposites - Bağcıoğlu, Cüneyt. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
In recent years, polymeric nanocomposites received large attention due to their superior mechanical, thermal, and optical properties as compared to micro-composites and neat polymers. Therefore, the main objective of this study was to prepare and characterise high performance polypropylene nanocomposites (PPNCs) containing organophilic layered nanosilicate (Org-MMT) and compatibilizer (coupling agent) by means of melt extrusion in a twin-screw extruder in order to investigate the role of organoclay content and compatibilizer addition on nanocomposite structure, morphology, and mechanical properties. Special attention was paid to design and synthesis of high performance polypropylene (PP) nanocomposites by choosing appropriate compatibilizers which are suitable for both stiffening/toughening and intercalation/exfoliation mechanisms. For this purpose, maleic anhydride grafted polypropylene (PP-g-MA) and maleic anhydride grafted ethylenepropylene- diene-monomer (EPDM-g-MA) were used as compatibilizers. Especially, the latter one is believed to serve as a special toughener coupling agent. The resultant nanocomposites were characterized by using X-Ray Diffraction (XRD), Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA), Dynamic Mechanical Analysis (DMA) and Static Mechanical Analysis including Tensile and Flexural as well as Izod Impact Testing methods.
Keywords: Polymeric composites.; Nanostructured materials.